1993
DOI: 10.1016/0270-9139(93)90239-j
|View full text |Cite
|
Sign up to set email alerts
|

Increased benzodiazepine-like activity is neither necessary nor sufficient to explain acute hepatic encephalopathy in the thioacetamide-treated rat

Abstract: Increased levels of natural benzodiazepine receptor agonists, produced in the body (endogenous) or ingested with food (exogenous) have been proposed as one of the factors causing hepatic encephalopathy in both experimental animals and human subjects. However, the divergent response of hepatic encephalopathy to benzodiazepine antagonists sheds doubt on this attractive hypothesis. Acute liver failure was induced in male Sprague-Dawley rats (n = 17) with intraperitoneal thioacetamide (600 mg/kg/day for 3 days) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Results of the present study demonstrated that such concentrations are sufficient to increase the binding of the GABA-A receptor agonist 3 H-muscimol to normal rat brain membranes, suggesting that the increased brain concentrations of these neurosteroids in PCA rats are of pathophysiological relevance. Previous studies showed that low nanomolar concentrations of allopregnanolone or THDOC increase the binding of 3 H-muscimol to normal rat brain cortical membranes, enhance muscimol-stimulated 36 Cl ) uptake in rat cerebral cortical synaptosomes, and increase GABA-activated chloride conductance in cultured neurons. [28][29][30][31] Moreover, the present study showed that brain extracts from PCA rats significantly increased the binding of 3 Hmuscimol compared to those from sham-operated controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the present study demonstrated that such concentrations are sufficient to increase the binding of the GABA-A receptor agonist 3 H-muscimol to normal rat brain membranes, suggesting that the increased brain concentrations of these neurosteroids in PCA rats are of pathophysiological relevance. Previous studies showed that low nanomolar concentrations of allopregnanolone or THDOC increase the binding of 3 H-muscimol to normal rat brain cortical membranes, enhance muscimol-stimulated 36 Cl ) uptake in rat cerebral cortical synaptosomes, and increase GABA-activated chloride conductance in cultured neurons. [28][29][30][31] Moreover, the present study showed that brain extracts from PCA rats significantly increased the binding of 3 Hmuscimol compared to those from sham-operated controls.…”
Section: Discussionmentioning
confidence: 99%
“…relevance of these compounds in HE has been questioned. 35,36 There is an increasing body of evidence to suggest an involvement of neurosteroids in brain complications of liver diseases. We recently demonstrated that allopregnanolone is accumulated in brains of patients who died in hepatic coma.…”
Section: Discussionmentioning
confidence: 99%
“…1). As discussed (2,4) we may have slightly overestimated tissue levels of benzodiazepine-like activity in both HE and control rats. Because benzodiazepine-like activity was very similar, it is difficult to explain the differences between the results of Basile et al in 1990 (3) and those of Wilder et al in 1993 (2) by an inadequacy of the extraction procedure alone.…”
Section: Replymentioning
confidence: 85%
“…Some experimental HE models that exhibited changes in neurotransmitters and receptors have been reported (1). For example, it has been reported that depression of consciousness and reduction of locomotor activity correlated with the activity of some neurotransmitters in a thioacetamide-induced ALF rat model (2)(3)(4). Furthermore, it has been shown that neural amino acids and N-methyl-D-aspartate receptors change in the rat brain concomitant with depression of consciousness in an ALF model induced by portacaval anastomosis followed 24 h later by hepatic artery ligation (5).…”
mentioning
confidence: 99%